Supernova: A Deoxyribozyme that Catalyzes a Chemiluminescent Reaction - Svehlova, Katerina; Lukšan, Ondřej; Jakubec, Martin; Curtis, Edward A (Angewandte Chemie (International ed. in English), 2022)
Functional DNA molecules are useful components in nanotechnology and synthetic biology. To expand the toolkit of functional DNA parts, in this study we used artificial evolution to identify a glowing deoxyribozyme called Supernova. This deoxyribozyme transfers a phosphate from a 1,2-dioxetane substrate to its 5' hydroxyl group, which triggers a chemiluminescent reaction and a flash of blue light. An engineered version of Supernova is only catalytically active in the presence of an oligonucleotide complementary to its 3' end, demonstrating that light production can be coupled to ligand binding. We anticipate that Supernova will be useful in a wide variety of applications, including as a signaling component in allosterically regulated sensors and in logic gates of molecular computers.
Keywords: chemiluminescence; deoxyribozyme; aptazyme; luminescence; catalytic DNA; in vitro selection; sensor